Management of Village Fund Allocation in Timbong Village, Central Banggai Subdistrict, Banggai Laut Regency - Ronaldo; Alamsyah, M. Nur; Hi. Ambotuo, Moh. Tabran (Journal of Public Administration and Government, 2024)
This study aims to understand how the village fund allocation is managed in Timbong Village, Central Banggai Subdistrict, Banggai Laut Regency. The research utilizes George R. Terry's theory, which divides management into four basic functions: planning, organizing, actuating, and controlling. A qualitative approach with a descriptive type is employed in this study. Data collection techniques include observation, interviews, and documentation, with the selection of seven informants chosen purposively. The findings indicate that the management of village fund allocation in Timbong Village, Central Banggai Subdistrict, Banggai Laut Regency, is hindered by insufficient communication among the village government, the Village Consultative Body (VCB), and the community, resulting in incomplete oversight by the Village Consultative Body and the community.